VENOUS THROMBOEMBOLIC COMPLICATIONS IN LYMPHOMA PATIENTS - Vladimir,; Mihaljević, Biljana; Antić, Darko (Medicinski podmladak, 2020)
Lymphomas represent a heterogeneous group of malignant hematological diseases characterized by a high risk for development of venous thromboembolic complications (VTE). Consequently, VTE significantly impacts on the morbidity and mortality of these patients. Another concern is the financial burden of the health system caused by diagnostic and therapeutic procedures of cancer-associated thrombosis (CAT). The complex biology of lymphoma, in conjunction with patient and treatment related risk factors for the development of VTE, results in a procoagulant hemostatic dysregulation. Considering the incidence of VTE in patients with lymphoma, there is an emerging demand for both reliable risks assessment model (RAM) for prediction of VTE and for effective VTE prophylaxis and treatment. The clinical course of the patients with malignant diseases is accompanied by a wide range of potential treatment complications, therefore the task of prevention and treatment of VTE becomes even more challenging. In recent years, great progress has been achieved in understanding the pathophysiological mechanisms of thrombotic complications, while the significant number of randomized controlled trials (RCT) have provided us with standards of prophylaxis and treatment of VTE complications in patients with malignancy. In comparison to previous recommendations and guidelines for CAT, the use of direct oral anticoagulants (DOAC) has been gradually approaching low molecular weight heparins (LMWH) in terms of efficacy and safety profile in these indications. This systematic review is focused on the latest pathophysiological advances, risk factors assessment, prophylactic and therapeutic recommendations and guidelines concerning VTE in patients with lymphoma.
Keywords: lymphomas, VTE, thromboprophylaxis, LMWH, DOAC